BD56, an Early-maturing and Drought-tolerant Variety for Bangladesh: Results from a Pilot Evaluation - CGIAR Standing Panel on Impact Assessment (CGIAR Standing Panel on Impact Assessment, 2016)
Kyle Emerick (Tufts), Alain de Janvry (UC Berkeley), Elisabeth Sadoulet (UC Berkeley), and Manzoor Dar (IRRI) initiated a pilot evaluation of BD56 starting in the 2015 wet season. BD56 is a recently released rice variety of IRRI that offers both early maturity and drought tolerance. This Brief presents results from the pilot evaluation funded by SPIA. The researchers are currently running a larger experiment in 256 villages in the Rajshahi division of Bangladesh, also funded by SPIA.